2018
DOI: 10.1016/j.apenergy.2018.09.166
|View full text |Cite|
|
Sign up to set email alerts
|

Numerical analysis of operating range and SOFC-off-gas combustor requirements of a biogas powered SOFC-MGT hybrid power plant

Abstract: Hybrid Power plants (HyPP) combining a micro gas turbine with a solid oxide fuel cell are projected to reach very high electric efficiency values. Powered by biogas, they have the potential to become an important pillar for a future CO 2-neutral energy mix. However, to compensate the fluctuating energy yield of wind turbines and photovoltaic power plants they should also provide a wide operating range. While previous numerical studies show that this is the case for natural gas powered HyPP, the impact of bioga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The four parameters considered were air-steam mixtures as reforming agents, fuel utilization factor, turbine inlet temperature, and compression ratio, and the several sets of information resulting from the analysis represent valuable knowledge for direct-biogas SOFC operational performance. Krummrein et al [74] investigated the performance related to the use of biogas fuel for their hybrid power plant SOFC-MGT demonstrator. Results of steady state simulations showed that the thermodynamic parameters are only slightly influenced by the substitution of methane with biogas.…”
Section: Sofc-mgt Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The four parameters considered were air-steam mixtures as reforming agents, fuel utilization factor, turbine inlet temperature, and compression ratio, and the several sets of information resulting from the analysis represent valuable knowledge for direct-biogas SOFC operational performance. Krummrein et al [74] investigated the performance related to the use of biogas fuel for their hybrid power plant SOFC-MGT demonstrator. Results of steady state simulations showed that the thermodynamic parameters are only slightly influenced by the substitution of methane with biogas.…”
Section: Sofc-mgt Systemsmentioning
confidence: 99%
“…In Table 5, a summary of the literature reviewed in this subsection has been listed. Performance maps [74] Turbec T100 ChemCAD TIT variability with SOFC (Subroutines for SOFC and gasifier?) [75] Turbec T100 Aspen Plus [76] 4.3.…”
Section: Sofc-mgt Systemsmentioning
confidence: 99%
“…Pressurizing the gases in the compressor prior to entering the SOFC raises the electrical efficiency of the SOFC [81]. This approach can be a high electrical efficiency option, especially for small-scale CHP [82]. Use of these combined systems is also being explored for auxiliary power units in the transportation sector [83].…”
Section: Combined High Temperature Fuel Cell With Gas Turbinementioning
confidence: 99%
“…Antonucci investigated the acceptable cost of sodium chloride nickel cell hybrid system using SOFC [15]. Krummrein proposed a detailed numerical model of hybrid system (SOFC + micro turbine), and discussed the influence of fuel cell operation limit on the operation range of hybrid power station, including stack temperature, minimum stack voltage, and maximum fuel utilization [16]. Lee used a simplified two-dimensional axisymmetric model domain to simulate the performance of a 1 kW fuel cell reforming unit.…”
Section: Introductionmentioning
confidence: 99%